(untitled) (Филолошки студии, 2019)
The article touches upon the most significant Anna Akhmatova’s work “The Poem without a Hero” that appeared to follow “Requiem” in poetic interpretation of evangelic theme of Crucifixion in the light of tragic destiny of the generation. To show the reflection of the Apocalyptic myth the author of the article researches the biblical cues of the poem, which is penetrated with gospel images, allusions, reminiscences from Genesis. They all, refracted through the prism of apocalyptic eschatology, reconstruct the Time – the prethunderstorm atmosphere of 1913, mirror the sensation of impendent Retribution. Special attention is paid to the key images of the poem – the image of Chalice. Being a poetical reflection of the biblical symbol of Crucifixion, the image of Chalice in Akhmatova’s poetic space is urged to explicit the idea of the generation’s destiny, propitiatory sacrifice.